Determinan Produksi Perikanan Nelayan Tangkap di PPN Pengambengan, Kecamatan Negara, Kabupaten Jembrana - Azhari, Kadek Ayu Novi; Santi, Ni Wayan Ayu (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to determine the influence of natural resources (X1), capital (X2), labor (X3), and skills (X4) on the production (Y) of capture fisheries in PPN Pengambengan, Negara District, Jembrana Regency. The research employs a quantitative approach with multiple linear regression analysis. The population in this research are the registered fishing groups at PPN Pengambengan, totaling 46 groups. The 46 fishermen group leaders were selected as the research sample using the purposive sampling technique. Data collection was conducted using a questionnaire that had undergone validity and reliability testing. The results of the study indicate that the natural resources variable (X1) has a significance value of 0.000 < 0.05, the capital variable (X2) has a significance level of 0.000 < 0.05, the labor variable (X3) has a significance level of 0.009 < 0.05, and the skills variable (X4) has a significance level of 0.000 < 0.05. The F significance level is 0.000 < 0.05. These findings indicate that all independent variables have a significant effect, both partially and simultaneously, on the dependent variable (production).